(untitled) (Research, Society and Development, 2025)
Pyometra is a prevalent gynecological emergency in small animal clinics, characterized by the accumulation of purulent secretion in the uterine lumen, which is commonly associated with hormonal dominance of the luteal phase, in which the action of progesterone favors endometrial proliferation and bacterial infection, often by Escherichia coli. Although it is more common in middle-aged or elderly dogs, the objective of this study is to describe and analyze a clinical case of pyometra in a young, four-year-old mixed-breed dog, detailing the diagnostic findings and therapeutic management performed at the Veterinary Teaching Clinic of the Maurício de Nassau University Center in Cacoal (RO). The blood count revealed marked leukocytosis, consistent with an infectious process, and the ultrasound showed distension of the uterine horns with liquid content, consistent with pyometra. Given the emergency, ovariohysterectomy (OHS) was indicated and performed as curative treatment. The patient underwent a standard anesthetic and surgical protocol, with total removal of the uterus and ovaries, and showed good postoperative progress. The case reinforces the importance of clinical suspicion and early diagnosis of pyometra, confirmed by complementary tests, even in young females with nonspecific signs. It is concluded that immediate surgical intervention is crucial in these patients to ensure a favorable prognosis.